COMPARATIVE STUDY OF ANTIDEPRESSANT-LIKE EFFECT OF THE LEAVES OF SAPINDUS EMARGINATUS AND ACORUS CALAMUS IN EXPERIMENTAL ANIMAL MODELS - SHOUGRAKPAM, PRIYADARSHINI; BHATTACHARJEE, ABHISHEK; MEDHABATI, MAYANGLAMBAM; GUNINDRO, NGANGOM (International Journal of Current Pharmaceutical Research, 2021)
Objective: Depression is an affective disorder characterized by a change in mood, lack of confidence, lack of interest in surroundings and many natural products that have been tried to treat the disease. The study was aimed to evaluate and compare the antidepressant activity of methanol leave extract of SapindusemarginatusVahl. (MESE) and Acoruscalamus Linn. (MEAC) in experimental models in albino mice. Methods: Methanol Extracts of the plants were prepared by soxhlet extraction method. Forced swimming test (FST) and Tail suspension test (TST) models were chosen to evaluate antidepressant activity.Albino mice were selected and divided into six groups of six animals for each experimental model. Group I received 1% gum acacia in distilled water (DW) at a dose of 1 ml/100 g orally. Group II received sertraline-10 mg/kg orally. Group III and IV were administered 200 and 400 mg/kg of MESE respectively. Group V and VI were treated with 200 and 400 mg/kg of MEAC, respectively. Results: Methanol extracts of Sapindusemarginatus and Acoruscalamus at the two different doses of 200 and 400 mg/kg demonstrated a significant decrease in immobility time when compared with the control in both animal models. The extracts at the higher dose of 400 mg/kg revealed a significant reduction in immobility time compared to 200 mg/kg of the same extract. Conclusion: The results suggest that the methanol extracts of SapindusemarginatusVahl. andAcoruscalamus Linn. possessthe anticonvulsant activityand justify their use in folk medicine.